THE ROLE OF ECOLOGICAL COMPETENCE IN THE MORAL DEVELOPMENT OF MEDICAL EDUCATION STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In this article observed a number of problems of environmental education are currently relevant. In order to improve the quality of the environment, which is one of the problems, the formation of personal participation skills, attitudes, values, and motivation in solving environmental problems was explained to the students of medical education.